2019 Canadian guideline for physical activity throughout pregnancy. Issue 21 (18th October 2018) - Mottola, Michelle F; Davenport, Margie H; Ruchat, Stephanie-May; Davies, Gregory A; Poitras, Veronica J; Gray, Casey E; Jaramillo Garcia, Alejandra; Barrowman, Nick; Adamo, Kristi B; Duggan, Mary; Barakat, Ruben; Chilibeck, Phil; et al.
Abstract : The objective is to provide guidance for pregnant women and obstetric care and exercise professionals on prenatal physical activity. The outcomes evaluated were maternal, fetal or neonatal morbidity, or fetal mortality during and following pregnancy. Literature was retrieved through searches of MEDLINE, EMBASE, PsycINFO, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, Scopus and Web of Science Core Collection, CINAHL Plus with Full Text, Child Development & Adolescent Studies, Education Resources Information Center, SPORTDiscus, ClinicalTrials.gov and the Trip Database from inception up to 6 January 2017. Primary studies of any design were eligible, except case studies. Results were limited to English-language, Spanish-language or French-language materials. Articles related to maternal physical activity during pregnancy reporting on maternal, fetal or neonatal morbidity, or fetal mortality were eligible for inclusion. The quality of evidence was rated using the Grading of Recommendations Assessment, Development and Evaluation methodology. The Guidelines Consensus Panel solicited feedback from end users (obstetric care providers, exercise professionals, researchers, policy organisations, and pregnant and postpartum women). The development of these guidelines followed the Appraisal of Guidelines for Research and Evaluation II instrument. The benefits of prenatal physical activity are moderate and no harms were identified; therefore, the difference between desirable and undesirable consequences (net benefit) is expected to be moderate. The majority of stakeholders and end users indicated that following these recommendations would be feasible, acceptable and equitable. Following these recommendations is likely to require minimal resources from both individual and health systems perspectives.